A Case of Feline Panleukopenia in Malaysia Confirmed by Electron Microscopy - Abdul Rahman, Sheikh Omar; Awang Iskandarzulkarnian, Pengiran Rayari; Ibrahim, Abdul Latiff; Cheng, B. Y. (1984)
A typical case of feline panleuk0penia in ~n 18 ;month-old domestic ca~ is repoted. The disease was characterised clinically by anorexza, depresszon, diarrhoea and dehydratzon. Typzcal pathologzcal changes of severe villous atrophy and erosion of the small intestial epitheliun were o~served. Electron microscopic examination of the faeces revealed the presence of partzcles resemblzng parvovzrus.